Efektivitas Teknik Pomodoro dalam Mereduksi Kebosanan Akademik pada Pembelajaran Literasi Siswa Sekolah Dasar - Ardilah, Rizka; Affandi, Ghozali Rusyid (Universitas Muhammadiyah Magelang, 2025)
Academic boredom has become a significant psychological phenomenon affecting literacy learning in elementary schools, characterized by unpleasant emotional experiences, cognitive deficits, and reduced motivation. This study aims to examine the effectiveness of the adapted Pomodoro Technique in reducing academic boredom in literacy learning among fifth-grade students. This research employed a true experimental design with a pretest-posttest control group involving 53 fifth-grade students at SDN Krembung 1, randomly assigned to experimental (n=27) and control (n=26) groups. The experimental group received the Pomodoro Technique intervention (15 minutes focus, 5 minutes break) for 6 weeks, while the control group received conventional learning. Academic boredom was measured using the adapted Achievement Emotions Questionnaire Academic Boredom Subscale (α=0.906). Data were analyzed using paired t-test, independent t-test, and Cohen's d. The results showed a highly significant reduction in academic boredom scores in the experimental group (M=-12.22, SD=4.19, 20.70% decrease) compared to the control group (M=-1.65, SD=2.02, 2.87% decrease). Independent t-test revealed a very significant difference (t=-5.91, p<0.001) with a very large effect size (Cohen's d=-1.63), indicating that the Pomodoro Technique is 7.36 times more effective than conventional learning in reducing academic boredom. The adapted Pomodoro Technique is highly effective in reducing academic boredom in elementary school literacy learning, providing evidence-based solutions to support quality education goals aligned with Sustainable Development Goals 4 achievement.